MODELING OF ROUGH ROTARY MILLING OF CRANKSHAFT PINS - Kacper CIEŚLAR; Stanisław PŁONKA (Scientific Journal of Silesian University of Technology. Series Transport)
The development of the modern automotive industry requires a quick adaptation of new production methods. This is possible thanks to software capable of simulating manufacturing processes. The paper discusses the modeling of the machining operation of a crankshaft’s crankpins for a diesel engine with the use of the planetary milling method. i.e., modeling of milling operation when a disc milling cutter, having its cutting inserts directed inwards, is performing rotary motion, and at the same time, the axis of this milling cutter circulates around the axis of a machined crankpin. For this purpose, a geometrical model of the machining of the crankshaft’s crankpin has been developed. Based on the design documentation of the crankshaft of the 4C90 type diesel engine and the documentation of the Steyr internal disc milling cutter, their CAD models have been developed, and the both models were linked together with suitable kinematic dependencies. In the next step, the crankpin having a length of 25 mm was divided by planes (in quantity lp=21) into 1.25 mm sections. On the main cutting edge of two cutting inserts of the disc milling cutter, points were marked at intersection locations with these planes. Using the Inventor 2016 system, twelve spline curves have been generated for each plane because each plane intersects 12 cutting inserts mounted in cassettes positioned around the circumference of the body of the disc milling cutter. Next, the spline curves were brought to a common coordinate system, rotating them at an angle resulting from the positioning of the cassettes with cutting inserts in the body of the disc milling cutter. Prepared in such a way, spline curves were written in dwg format, which allowed for trimming of the spline curves at the circle with a radius of rcp = 27.90 mm, corresponding to the radius of the crankpin after milling, considering grinding allowance (ø55h6 + 0.80 mm grinding allowance). As a result, it enabled to leave sections of the arcs tangential to the diameter ø55.80 mm and, in such a way, generate the outline of the shape of the crankpin using the REGION command for 21 cross-sections. The outline of the cylindricity of the crankpin was obtained using the strategy of outlines of the roundness, which were generated earlier; this strategy consisted in the collection of 360 points on the circumference of 21 mutually parallel sections cut by planes perpendicular to the axis of the crankpin. To determine the effects of the circular feed rate of the circulating move of the axis of rotation of the internal disc milling cutter on the accuracy of the machining, simulations of the shape of the crankpin were performed for three values of the feedrate: vf = 1200 mm/min; vf = 2100 mm/min and vf = 3000 mm/min. The spline curves with a determined (depending on the duration of the simulation) number of points: 3500, 2100 and 1409 were obtained for each simulation. The calculated cylindricity deviation for the feedrate vf = 1200 mm/min amounted to CYLrck = 0.2272 mm, for the feedrate vf = 2100 mm/min – CYLrck = 0.2406 mm, while for the feedrate vf = 3000 mm/min – CYLrck = 0.2929 mm.